Penerapan Accelerated Learning dan Pemanfaatan Gelombang Otak Alfa untuk Meningkatkan Kemampuan Membaca Pemahaman dan Motivasi Belajar - Ade Wijaya; Anindita Puspita (FKIP UNIVERSITAS PAKUAN, 2016)
The research entitles Learning Management Using Accelerated Learning Approach and the Use of Alfa Brain Wave to Improve Reading Comprehension and Learning Motivation of Class VIII Zainab Students of SMP IT Rahmaniyah. The research was conducted in two cycles and there were four activities in each cycle: planning, doing, observing, and reflecting. The first cycle consisted of two treatments using accelerated learning and the use of alfa brain wave. In the first cycle, students’ score of Bahasa Indonesia subject was not optimal. The average score of the first cycle was 81.72. In the second cycle, there was an improvement of students’ score into 88.35. The classical score of students’ motivation in the first cycle was 74.19% and it was improved in the second cycle into 100%. From the research, it can be concluded that learning management using accelerated learning approach and the use of alfa brain wave is able to improve the ability of reading comprehension and learning motivation of class VIII Zainab students of SMP IT Rahmanyah